Silver-Russell Syndrome (RSS) in a 16-year old boy with atrial and ventricular septal defect (ASD, VSD) - Jancevska, Aleksandra; Kirovski, Ilija; Jovanov, Gjorgji; Zafirovski, Gjorgi; Tasic, Velibor; Gucev, Zoran (My University, 2006)
A four years old boy was referred for dysmorphic features: a broad, prominent forehead with small triangular face, small narrow chin, divergent strabism, low set ears, short neck, clinodactyly, and contractures of both elbows. His mental development was retarded. He attains a school for children with special needs. His gait and motor coordination is awkward. Cryptorchidism was surgically corrected. Physical examination with additional ultrasound revealed a congenital cardiopathy: atrial and ventricular septal defect (ASD, VSD). Both anomalies have been surgical corrected later. His birth weight and length were low, but he started growth delay in the early childhood attaining short stature at the time of his referral (-4.75 SD). His bone age was delayed for two years. Test of pituitary reserve revealed normal growth hormone levels (18.8 and 14.1 ng/ml). Sella turcica had double contoures. Treatment with growth hormone was started at the age of seven years. Growth velocity increased and after three years he attained the third percentile (-2 SD). In total he gained 2.75 SD making the treatment with GH successful. It has to be stressed that the effect of GH treatment was additionally hampered by the short familial stature (mother 159 cm, father 164 cm, target height 166 cm). Occasional reports of association of RSS with congenital cardiac anomalies are published. Still this association is rare. It is of note that GH treatment was successful in spite of normal GH concentrations on pituitary reserve tests. RSS, its association with other anomalies and the response of RSS to GH treatment are discussed in this paper.